The situational approach to vocational training of the teacher of the Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In article the essence of key concepts of research, their interrelation has been analyzed. Advisability of application of the situational approach in vocational training of the teacher of the Ukrainian language is determined. The main objective and the features of situational trend at practical lessons on the methods of the Ukrainian language teaching are characterized.
Keywords: the vocational training; the situational approach; the situational training